Community level impacts of invasive mosquitofish may exacerbate the impact to a threatened amphibian. (14th November 2017) - Klop‐Toker, Kaya; Valdez, Jose; Stockwell, Michelle; Clulow, Simon; Clulow, John; Mahony, Michael
Abstract: Invasive fish threaten many native freshwater fauna. However, it can be difficult to determine how invasive fish impact animals with complex life cycles as interaction may be driven by either predation of aquatic larvae or avoidance of fish‐occupied waterbodies by the terrestrial adult stage. Mosquitofish ( Gambusia spp.) are highly successful and aggressive invaders that negatively impact numerous aquatic fauna. One species potentially threatened by Gambusia holbrooki is the green and golden bell frog ( Litoria aurea ). However, G. holbrooki's role in this frog's decline was unclear due to declines driven by the chytrid fungal disease and the continued co‐existence of these fish and frogs in multiple locations. To clarify the extent to which Gambusia is impacting L. aurea, we conducted 3 years of field surveys across a deltaic wetland system in south‐east Australia. We measured the presence and abundance of aquatic taxa including G. holbrooki, and L. aurea frogs and tadpoles, along with habitat parameters at the landscape and microhabitat scale. Generalized linear models were used to explore patterns in the abundance and distributions of L. aurea and G. holbrooki . We found strong negative associations between G. holbrooki and tadpoles of most species, including L. aurea, but no apparent avoidance of G. holbrooki by adult frogs. Native invertebrate predators (Odonata and Coleoptera) were also absent from G. holbrooki ‐occupied ponds. Due to the apparent naivety of adult frogs toward G. holbrooki, the separation of G. holbrooki and tadpoles, plus the abundance of alternative predators in G. holbrooki ‐free ponds, we conclude that the impact of G. holbrooki on L. aurea recruitment is likely substantial and warrants management action.